Economic evaluation of mobile phone text message interventions to improve adherence to HIV therapy in Kenya. Issue 7 (February 2017) - Patel, Anik R.; Kessler, Jason; Braithwaite, R. Scott; Nucifora, Kimberly A.; Thirumurthy, Harsha; Zhou, Qinlian; Lester, Richard T.; Marra, Carlo A.
Abstract: Background: A surge in mobile phone availability has fueled low cost short messaging service (SMS) adherence interventions. Multiple systematic reviews have concluded that some SMS-based interventions are effective at improving antiretroviral therapy (ART) adherence, and they are hypothesized to improve retention in care. The objective of this study was to evaluate the cost-effectiveness of SMS-based adherence interventions and explore the added value of retention benefits. Methods: We evaluated the cost-effectiveness of weekly SMS interventions compared to standard care among HIV+ individuals initiating ART for the first time in Kenya. We used an individual level micro-simulation model populated with data from two SMS-intervention trials, an East-African HIV+ cohort and published literature. We estimated average quality adjusted life years (QALY) and lifetime HIV-related costs from a healthcare perspective. We explored a wide range of scenarios and assumptions in one-way and multivariate sensitivity analyses. Results: We found that SMS-based adherence interventions were cost-effective by WHO standards, with an incremental cost-effectiveness ratio (ICER) of 1, 037/QALY. In the secondary analysis, potential retention benefits improved the cost-effectiveness of SMS intervention (ICER = 864/QALY). In multivariate sensitivity analyses, the interventions remained cost-effective in most analyses, but the ICER was highly sensitive to intervention costs, effectiveness and average cohort CD4 count at ART initiation. SMS interventions remained cost-effective in a test and treat scenario where individuals were assumed to initiate ART upon HIV detection. Conclusions: Effective SMS interventions would likely increase the efficiency of ART programs by improving HIV treatment outcomes at relatively low costs, and they could facilitate achievement of the UNAIDS goal of 90% viral suppression among those on ART by 2020. Abstract : Supplemental Digital Content is available in the text